Persistence in the cryptocurrency market - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Alex Plastun (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper examines persistence in the cryptocurrency market. Two different longmemory methods (R/S analysis and fractional integration) are used to analyse it in the case of the four main cryptocurrencies (BitCoin, LiteCoin, Ripple, Dash) over the sample period 2013-2017. The findings indicate that this market exhibits persistence (there is a positive correlation between its past and future values), and that its degree changes over time. Such predictability represents evidence of market inefficiency: trend trading strategies can be used to generate abnormal profits in the cryptocurrency market.
Keywords: C22; G12; 330; crypto currency; BitCoin; persistence; long memory; R/S analysis; fractional integration